Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/07410883211069057
|View full text |Cite
|
Sign up to set email alerts
|

Understandings of the Role of the One-to-One Writing Tutor in a U.K. University Writing Centre: Multiple Perspectives

Abstract: This article presents findings from a study of a U.K. university writing centre regarding understandings of tutor roles, involving 33 Chinese international students, 11 writing tutors, and the centre director. The research used interviews and audio-recorded consultations as data to analyze and explore participants’ beliefs and understandings. The most common roles associated with tutors were proofreader, coach, commentator, counsellor, ally, and teacher. Mismatches were found in understandings of the proofread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, based on the dialectical relationship between conceptual understanding and learners' writing competence revealed in this study, I suggest a linguistically responsive approach to writing instruction that provides abundant linguistic support and acknowledges and leverages learners' linguistic diversity. This study advocates for the pedagogical discussion that calls for renewed attention to language support in L2 writing and tutoring contexts for academic purposes, which are currently dominated by a philosophy that focuses on higherorder concerns (e.g., content, organization, purpose) over the lower-order concerns (various levels of language, mechanics, and punctuation) in L2 writing (Ferris & Eckstein, 2020;Liu & Harwood, 2022). L2 Journal Vol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on the dialectical relationship between conceptual understanding and learners' writing competence revealed in this study, I suggest a linguistically responsive approach to writing instruction that provides abundant linguistic support and acknowledges and leverages learners' linguistic diversity. This study advocates for the pedagogical discussion that calls for renewed attention to language support in L2 writing and tutoring contexts for academic purposes, which are currently dominated by a philosophy that focuses on higherorder concerns (e.g., content, organization, purpose) over the lower-order concerns (various levels of language, mechanics, and punctuation) in L2 writing (Ferris & Eckstein, 2020;Liu & Harwood, 2022). L2 Journal Vol.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in our study highlighted the crucial role of supervisors in completing a thesis study from the perspectives of the supervisees. In the literature as well, this central role was emphasised by many studies on thesis writing, and similar attributes were defined for supervisors (Fitria, 2022;Liu and Harwood, 2022;White, 1998;Wisker et al, 2003;Zhang and Hyland, 2021). Fitria (2022), in this sense, found the supervisor as the primarily responsible figure for guiding students to write acceptable theses while Zhang and Hyland (2021) suggested that the process of supervision itself was decisive for students to get the sense of producing knowledge in their subject fields.…”
Section: Theme 1: Supervisor Supportmentioning
confidence: 97%
“…Regarding the impact of the supervisor, supervision accommodates power that directly influences the quality of the thesis product and the successful completion of it (Chang, 2007;Frischer and Larsson, 2000;Zhang and Hyland, 2021). With this regard, the roles of a supervisor were specified as "team leader, project manager, writing mentor, wordsmith, and editor" (White, 1998:229) while Liu and Harwood (2022) found that proofreader, coach, commentator, counsellor, ally, and teacher were the common roles associated with supervisors. Zhang and Hyland (2021), on the other hand, highlighted that supervisors can be negotiators, collaborators, and facilitators providing advice and giving students the freedom to reflect on their own ideas.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some universities offer a free in-house proofreading service, such as the one in the University of Essex’s sociology department described in Harwood et al (2009). Furthermore, although classic university writing center policy debars proofreading (see North, 1984), some writing centers offer it in some form (see Liu & Harwood, 2022a, 2022b). Students may additionally access proofreading from friends, peers, and relatives, or use one of the many paid-for proofreading services available online.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing squarely on the student writing context, there have been investigations of the work of commercial proofreading agencies, the knowledge and competence of proofreaders, and the types of (frequently unethical) intervention requests students make of proofreaders (Lines, 2016). And there have been investigations located in university writing centers, which traditionally claim to eschew proofreading (see Brooks, 1991;North, 1984), to determine the extent to which writing center tutors do or should in fact proofread (Clark & Healy, 2008;Eckstein, 2013;LaClare & Franz, 2013;Mack, 2014;Moussu, 2013;Moussu & David, 2015;Liu & Harwood, 2022a, 2022b.…”
Section: Introductionmentioning
confidence: 99%